On the Possibility of Stock Market Crashes in the Absence of Portfolio Insurance - Gadi Barlevy; Pietro Veronesi (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
stock market crash on hedging strategies by portfolio insurers, which dictated selling stocks as soon as prices fell. The fact that the practice of buying and selling stocks as portfolio insurance has virtually disappeared since then has given many comfort that a replay of the 1987 crash, when prices fell so much so quickly, is unlikely. This note argues with this view by developing a model in which crashes are possible in the absence of portfolio insurance. In our model, a crash is driven by panic selling among rational but uninformed traders.
Keywords: G14; D82; D84; 330; Giffen Effect; Portfolio Insurance; Hedging Demand; Market Crashes